Critical literature reviews: A critique and actionable advice. Issue 2 (April 2023) - Wright, Alex; Michailova, Snejina
This article treats critical literature reviews as a distinct review type, and presents a critique of author-labeled critical literature reviews in Organization and Management Studies. We identify and problematize 275 review articles that claim to critically review a body of literature and find that most to not deliver on this claim. Many critical literature reviews do not adequately explain what is meant by "critical" and are highly uncritical in their execution. We reveal the following two significant problems: lack of construct clarity and a prevailing "group, re-present, and summarize" approach. We also identify 19 exemplary critical literature reviews—those that exhibit judgment about the literature they cover. These are drawn from across the onto-epistemological spectrum, so include works from within both the positivist and interpretivist traditions. We propose a "Call for Action" aimed at authors, reviewers, and editors to increase critical literature reviews' quality and impact. We enhance the long tradition within Management Learning for improving scholarship and focus on a skill all academics are required to learn, exercise, and demonstrate—to conduct high-quality literature reviews.